ANÁLISE DAS FALHAS DE AUDITORIAS DO SISTEMA LEAN: ESTUDO DE CASO EM EMPRESA CONSTRUTORA - Angelim, Vanessa Lira; Lima, Romario Xavier de; Sales, Cordeiro Helder de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In the face of the comprehensive implementation of lean principles in the construction industry, companies began to formalize lean system procedures. In order to promote continuous improvement of processes, there is a need to evaluate through audits the level of attendance to lean requirements. In this way, the present work has the objective of analyzing the data of the audits of the lean system in 15 buildings of a construction company located in Brazil and identify the main faults and opportunities for improvement. The audits were carried out during 6 bi-monthly cycles in the year 2017. The results indicate that, despite the company's efforts to standardize the lean procedure in its works, to plan the workflow in a more optimized way, there are failures in the accomplishment of the lean activities by the employees and difficulty in obtaining the commitment and the understanding by the teams of about lean principles. The suggested improvement opportunities are more investments in training and implementation of motivational factors to get more commitment from employees. In addition, conducting lean audits were important to obtain data that guide corrective and preventive actions and promote the continuous improvement of company processes.